Etična občutljivost študentov zdravstvene nege - Renko, Jakob (Obzornik zdravstvene nege, 2023)
Introduction: Ethical sensitivity is an important factor in providing quality health care. The aim of this study was to measure ethical sensitivity of undergraduate nursing students.Methods: A quantitative research methodology with surveying was used. The survey was administered to a convinience sample of 126 undergraduate nursing students. Data were collected using a translated and adapted Ethical Sensitivity Questionnaire for Nursing Students. The following methods were used for statistical analysis: basic descriptive statistics, non-parametric Mann-Whitney U-test and the Kruskal-Wallis H-test.Results: The internal consistency value for the entire questionnaire showed a good level of reliability (Cronbach ? = 0.711). The undergraduate nursing students showed a moderate level of ethical sensitivity (= 33.50, p = 5.615). The results showed statistically significant differences in the level of ethical sensitivity of full-time undergraduate nursing students compared to part-time students (p = 0. 025).Discussion and conclusion: It was concluded that there are opportunities to improve ethical sensitivity of nursing students. Based on the results, further research on ethical sensitivity related to work-related indifference in the health care system is needed. It would also be useful to compare ethical sensitivity of nursing students and registered nurses to explore the factors that influence ethical sensitivity.
Keywords: dodiplomski študij; ethical dilemmas; etične dileme; nursing; profesionalne vrednote; professional values; secondary socialization; sekundarna socializacija; undergraduate studies; zdravstvena nega